Temperature effects on the calcite skeletal composition of deep-water gorgonians (Isididae) - Thresher, Ronald E.; Wilson, Nicholas C.; MacRae, Colin M.; Neil, Helen (Geochimica et cosmochimica acta, 2010)
We test for and calibrate a proxy for ocean temperature based on the skeletal composition of the widely distributed, deep-sea gorgonians in the family Isididae (bamboo corals), through use of three complementary methods: a short-term comparison of element/Ca ratios to a four-year temperature record, a long-term comparison with oceanographic records spanning forty years, and a geographic comparison of Isidids collected at sites ranging from the tropics to Antarctica. The assays consistently support a temperature-dependency for Mg/Ca ratios and suggest S/Ca is indirectly affected by temperature, but indicate little or no effect of temperature on P/Ca and Sr/Ca. The consensus relationship between Mg/Ca and temperature for Isidid calcite from the comparisons with the temperature time-series is T = −0.505 + 0.048 Mg/Ca, where T is in °C, Mg/Ca is in mmol/mol, and the applicable range is 3–6 °C. The results of the geographic assay, though imprecise, suggest the applicable range extends to temperatures below freezing. The scatter of data points around the regression of temperature and Mg/Ca is wide in all assays. This could reflect the effect of factors other than temperature on Mg/Ca ratios, but is also likely to reflect limitations of the field data, the effects of assumed constant growth rates in the corals and instrumental analytical error. The combined effects of micro-scale variability in growth rates and wide confidence intervals for each data point suggests that environmental reconstruction from Isidid internode calcite from sparse data or at time scales less than decades be done with caution. Comparisons within and among colonies do not indicate strong vital effects on ontogenetic variability in the corals, other than possibly close to the central pore of the coral. However, similar Mg/Ca ratios for Isidids from Antarctic and more temperate regions suggest adaptation to local conditions and hence a role for physiology at higher taxonomic levels, at least. Taxonomically higher level vital effects are also suggested by large differences between gorgonian families in their regressions between Mg/Ca and temperature, by Mg/Ca ratios that overlap over a wide temperature and habitat range, and for a non-linear relationship between temperature and the slope of the Mg/Ca-temperature relationship across the order.